Variações no gene yolk em moscas das frutas do grupo fraterculus - Oliveira, Gustavo Castro de (2009)
Species of the fraterculus group are associated to the biggest damages to fruit crops due to the fact that they attack indiscriminately green and ripe fruits, making them pests of great economic importance. These species are hard to tell apart, even showing some potential criptic species. The understanding of the populational structure and biology of this species group is of paramount importance to strategies of management and control of these pests. Here, we investigate variation on the gene yolk em 37 individuals sampled throughout the species distribution in Brazil seeking to better understand the populational structure of this species group in Brazil. Our data indicated existence of recombination, which lead us to analyze three different regions in the gene, 5 , mid, and 3 . These regions show high levels of nucleotide diversity intra and interspecifically for all three gene regions investigated. The use of Nested Clade Phylogenetic Analysis independently used on these regions indicate two main results that occurred more than one throughout our analyses. The first is a range expansion from north-NE populations towards the south, mostly related to specimens of Anastrepha fraterculus. The second common event, detected eight times, is restricted gene flow with isolation by distance (IBD). Dating of such events indicated that they are temporarily congruent which might indicate that the lack of IBD in other levels of the analysis might be caused either by sampling limitations or an excess of local gene flow that tampers out as we move farther in space. Our results of the gene yolk have provided us with a better understanding of the levels of local variation of this marker of for the species that may help us determine the evolutionary processes that shaped the species group current distribution.